2022
DOI: 10.1177/00048674221086498
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of suicidality in young people with depressive disorders: A systematic review

Abstract: Objective: Depression is one of the most prevalent and disabling mental health conditions among young people worldwide. The health and economic burdens associated with depressive illness are substantial. Suicide and depression are closely intertwined, yet a diagnosis of depression itself lacks predictive specificity for suicidal behaviour. To better inform suicide prevention and early intervention strategies for young people, improved identification of modifiable intervention targets is needed. The objective o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 193 publications
0
4
0
Order By: Relevance
“…Selection of correlates in our analysis was conducted a priori based on previous comprehensive systematic review findings (Moller et al, 2022). However, our investigation was limited to the measures that were included in the YoDA trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selection of correlates in our analysis was conducted a priori based on previous comprehensive systematic review findings (Moller et al, 2022). However, our investigation was limited to the measures that were included in the YoDA trials.…”
Section: Discussionmentioning
confidence: 99%
“…Our selection of correlates was primarily based on recent systematic review findings characterising associations between suicidal outcomes and a broad range of psychosocial correlates in young people with clinically diagnosed depressive disorders (Moller et al, 2022). Treatment allocation was not included as a correlate, as the treatments under investigation in both YoDA studies did not result in any significant difference in clinical outcomes, compared with treatment as usual (Berk et al, 2020; Davey et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Suicidality is a transdiagnostic concept resulting from the interaction of various contributing factors ( 34 ). Our regression analysis revealed significant relations between the BDI scores and current C-SSRS scores.…”
Section: Discussionmentioning
confidence: 99%
“…Poor mental health is one of the main drivers of death by suicide (Cavanagh et al, 2003; Glaesmer et al, 2020; Moller et al, 2022; Roy et al, 2021). A systematic review and meta‐analysis of 203 studies showed that mortality due to unnatural causes (suicides and injuries) is seven times higher in patients with mental disorders compared to the general population (Walker et al, 2015).…”
Section: Introductionmentioning
confidence: 99%